A TAXONOMIC REVIEW AND A NEW SPECIES OF THE SOUTH AMERICAN WOODY GENUS AMBURANA (LEGUMINOSAE, PAPILIONOIDEAE) - Seleme, Elidiene P.; Lewis, Gwilym P.; Stirton, Charles H.; Sartori, Ângela L.b.; Mansano, Vidal F. (Phytotaxa, 2015)
A taxonomic revision of the South American genus Amburana comprised of three species is presented, including the new species A. erythrosperma which is described and illustrated. Amburana cearensis occurs widely in Argentina, Bolivia, Brazil and Paraguay.  Amburana acreana occurs in the Bolivian, Brazilian and Peruvian Amazon. Amburana erythrosperma is endemic to the southern Chapada Diamantina, Bahia, Brazil. The species are distinguished by the color of the stem, the number per leaf and shape of leaflets, the size of inflorescence, color and size of the standard petal, fruit with endocarp developed to form a papery wing surrounding the seed or this lacking, and color of seed. A key to the species is provided together with descriptions, taxonomic comments, geographical distribution maps and illustrations for each.  Lectotypes for A. acreana and A. cearensis are designated.